Potential Solutions Using Bacteriophages against Antimicrobial Resistant Bacteria - Aryan Rahimi-Midani; Seon-Woo Lee; Tae-Jin Choi (MDPI AG, 2021)
Bacteriophages are viruses that specifically infect a bacterial host. They play a great role in the modern biotechnology and antibiotic-resistant microbe era. Since the discovery of phages, their application as a control agent has faced challenges that made antibiotics a better fit for combating pathogenic bacteria. Recently, with the novel sequencing technologies providing new insight into the nature of bacteriophages, their application has a second chance to be used. However, novel challenges need to be addressed to provide proper strategies for their practical application. This review focuses on addressing these challenges by initially introducing the nature of bacteriophages and describing the phage-host-dependent strategies for phage application. We also describe the effect of the long-term application of phages in natural environments and other bacterial communities. Overall, this review gathered crucial information for the future application of phages. We predict the use of phages will not be the only control strategy against pathogenic bacteria. Therefore, more studies must be done for low-risk control methods against antimicrobial-resistant bacteria.